Methylglyoxal level in Type 2 Diabetes with Acute Myocardial Infarction and its Association with Systemic Hypertension (Medical Forum Monthly, 2024)
Background: The chronic hyperglycemia in type 2 diabetes mellitus (T2DM) is characterized by formation of a variety of toxic α-oxoaldehydes among which the methylglyoxal (MG) damages low density lipoproteins raising the possibility of atherogenesis upto fourfold is one proposed mechanism. The atheroma may then cause the coronary artery disease i.e. myocardial infarction and ischemic disease.Objective: To study the methylglyoxal levels in type 2 DM with acute myocardial infarction (AMI) compared normal controls and to assess its predictive significance.Study Design: comparative case control studyPlace and Duration of Study: This study was conducted at the Diabetic clinics of Isra University Hospital & other tertiary care hospitals in Hyderabad from _____.Materials & methods: Thirty normal controls (Group. I) and thirty type 2 diabetics with acute myocardial infarction (Group. II) were studied according to inclusion and exclusion criteria. 5.0 ml of blood was transferred into citrated bottles. Sera were obtained by centrifugation at 4000 rpm for 10 minutes and were frozen at -20 0C. The blood glucose (BS) level was detected by glucose oxidase method. MG was measured by the ELISA assay. Student`s t-test, Chi square test and Spearman`s correlations was used for the continous & categorical variables and linear association respectively. Data was collected on a proforma. Informed consent was taken from the participants. Study protocol was approved by the ethics committee of the institute. The Data was analyzed using SPSS version 17.0. A p-value of ≤0.05 was taken statistically significant.Results: The male and female ratio was noted as 0.57:1 and 1:2.7 and age of 51.9±5.0 and 53.5±6.8 years in controls and type 2 diabetics with acute myocardial infarction respectively. The random blood sugar was noted as 112.6±16.8 and 304±73.8 (mg/dl) in both groups respectively (p= 0.0001). Very high levels of BS (90%) indicate that most of patients are reluctant to glycemic control. Very high levels of MG were observed in T2DM with acute MI compared with normal healthy controls; 87.7±44.2 vs. 9.19±1.29 ng/ml. (p=0.0001). Hypertension was observed in 19 (63%) of diabetics and drug non-compliance was common; 26 (86%). A powerful Spearman`s correlations of MG was observed with of the BS, SBP and DBP (p = 0.0001).Conclusion: The present study provides evidence that MG is a predictor of acute myocardial infarction and elevation of systemic blood pressure in type 2 diabetics, suggesting its clinical usefulness as a biomarker for diabetic macroangiopathy.